(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigates the relationship between child labor and social exclusion in Multan, Southern Punjab, focusing on children engaged in agricultural and domestic labor. Using purposive sampling, the research examines the socio-cultural and economic factors driving child labor and its subsequent impact on educational access, healthcare, and social participation. The findings reveal that economic hardship and familial expectations are the primary drivers of child labor in the region. Poverty, coupled with the lack of viable employment opportunities for adults, forces many families to rely on the labor of their children to meet basic needs. As a result, a significant number of children are excluded from formal education, limiting their future opportunities and contributing to the perpetuation of the poverty cycle. Furthermore, children in labor-intensive sectors, such as agriculture, also face significant healthcare exclusions due to the inability to afford medical care or take time off from work. The social isolation of these children, who are unable to engage in recreational or educational activities, further deepens their marginalization. The study highlights the urgent need for targeted interventions that focus on poverty alleviation and increasing educational access for child laborers. Policy recommendations include the implementation of flexible schooling systems, community-based welfare initiatives, and the strengthening of legal frameworks to protect children’s rights. These measures can help reduce child labor and foster greater social inclusion in Southern Punjab.